The impacts of weather and climate information services on technical efficiency and farm productivity among smallholder farmers in the Upper West Region of Ghana - Djido, Abdoulaye; Houessionon, Prosper; Nikoi, Gordon; Ouédraogo, Issa; Ouédraogo, Mathieu; Segnon, Alcade C; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This study evaluates the impacts of a pilot project that introduced weather and climate information services (CIS) on technical efficiency (TE) and sorghum productivity (Y) using a total of 210 plotlevel data comprising of 92 users and 118 nonusers of CIS in the Upper West Region of Ghana. First, we estimate a Stochastic Frontier model to measure the level of TE using a Cobb-Douglas functional form with the assumption of an exponential distribution for the identification of TE scores. Secondly, we measure the impact of the adoption of CIS on TE and Y separately by addressing the potential bias stemming from the existence of unobserved characteristics using a Control Function estimator. Thirdly, we employ a Recursive Structural Equation System to deal with the simultaneous problems of the endogenous treatment of CIS into Y, the endogenous covariate of TE into Y, and the reverse causality between Y and TE. Overall, our findings are robust to the different methodologies with strong evidence that the pilot project through the adoption of CIS has a substantial positive effect on improving TE and Y in the study area. Our empirical results consistently estimate approximately 6% increase in TE and 35% sorghum yield improvement corresponding to 150 Kg/Ha increased productivity among CIS users. Furthermore, when we simultaneously estimate the combined effects of the adoption of CIS and the level of TE on sorghum productivity with and without the problem of reverse causation between Y and TE, the median value of the average treatment effects (ATE) is 10%. Also, improving the level of TE has a higher payoff among users than nonusers of CIS resulting in increased sorghum productivity of 5% when we compare the average treatment effects on the treated (ATET) and the average treatment effects on the untreated (ATEU). These results underscore a valuable policy insight and the importance of privileging the wide adoption of CIS and promoting the efficient use of inputs with best-recommended climate-smart agricultural practices such as crop management and increasing trainings to raise awareness in future project expansion. However, it appears that the magnitudes of the impacts of the adoption of CIS on Y using the ATE, ATET, and ATEU are sensitive to whether we address the potential reverse causality between Y and TE. These findings indicate that more caution should be considered in the evaluation of the impacts of a project that promotes agricultural innovations including information communication technologies on farm productivity and technical efficiency.